Exploring Citizenship: Unit 7 My World - John Rutledge; Joy C. Jordan; Dale W. Pracht (EDIS)
The 4-H Citizenship Project offers the opportunity to help 4-H members relate all of their 4-H projects and experiences to the world around them. The 4-H Citizenship manuals will serve as a guide for 4-H Citizenship experiences. To be truly meaningful to the real-life needs and interests of your group, the contribution of volunteer leaders is essential. Each person, neighborhood, and community has individual needs that you can help your group identify. This 14-page major revision of Unit VII covers the “My World” project. Written by John Rutledge, Joy C. Jordan, and Dale Pracht and published by the UF/IFAS Extension 4-H Youth Development program. https://edis.ifas.ufl.edu/4h021